not sure what your question is, but here's a quick n' dirty to solving simple algebraic equations:
we'll use this simple equation 5 - x = 4x
step 1: get all your variables on one side of the = and constants on the other... think of the = as a balance point on a balance scale... you can do anything to one side, and as long as you do it to the other, it will stay balanced!
so to get the x from 5 - x to the other side, we need to add an x to both sides: 5 - x + x = 4x + x, 5 - 0 = 5x, 5 = 5x
step 2: get the variable down to one multiplier
we know what 5x is, but we want to know x... so how do we find out? Well, since we know what 5 times x is, we can divide this by 5 to get x. But, we want to stay "balanced" so we have to divide both sides by 5:
5x / 5 = 5 / 5
x = 1
Voila! Solved :)
Hope this helps.
2006-11-10 10:53:17
·
answer #1
·
answered by disposable_hero_too 6
·
0⤊
0⤋
If you mean
1y = 7y (-1)(-1)(-1)(-1) 8
Then:
(We assume that there is a one in front of the variable if there is none listed.)
y = 7y + 8
move over 7y by subtracting it from both sides to collect common terms.
y-7y = 8
-6y = 8
divide it all by the coefficient in front of the variable
(-6y = 8)/(-6)
y = -8/6
2006-11-10 18:56:20
·
answer #2
·
answered by Anonymous
·
1⤊
1⤋
The answer is 1.33333y.
work:
1y = 7y ---- 8?
8+1y=7y
8=6y
2006-11-10 19:03:53
·
answer #3
·
answered by ihaveaquestion 2
·
0⤊
0⤋
if your question was 1y = 7y - 8 then it would be:
1y - 7y = -8
-6y = -8
y = -8/-6
y= 4/3
2006-11-10 18:54:30
·
answer #4
·
answered by Anonymous
·
2⤊
0⤋
y=7y-8
first subtract 7y in both sides to get y in one side
y = 7y - 8
-7y -7y
ur left w/ -6y=-8
divide by -6
and y = 4/3
2006-11-10 18:55:11
·
answer #5
·
answered by Jose G D 2
·
0⤊
0⤋
If the ------------ means+, then you first subtract 7y from each side and get -6y = 8 . Next divide each side by -6 and y = -4/3
If the------------means -, then you first subtract 7y from each side and get -6y = -8. Divide each side by -6 and y = 4/3
2006-11-10 18:54:58
·
answer #6
·
answered by MollyMAM 6
·
2⤊
0⤋
1y=7y-8
-7y=-7y-8
-6y= -8
y= -8/-6
2006-11-10 18:57:03
·
answer #7
·
answered by Anonymous
·
0⤊
0⤋